Heart rate variability and circulating catecholamine concentrations during steady state exercise in healthy volunteers. Issue 2 (August 1993) - Breuer, H W; Skyschally, A; Schulz, R; Martin, C; Wehr, M; Heusch, G
Abstract : OBJECTIVES–To assess whether exercise induced suppression of heart rate variability in the low frequency domain (0.06-0.15 Hz) is related to the increase in circulating catecholamine concentrations. DESIGN–Randomised crossover trial of three exercise tests characterised by different workloads. Pharmacological simulation of exercise-induced changes in vagal and sympathetic activity. PARTICIPANTS–Six healthy men with a mean age of 31.2 (SD 3.0) years. INTERVENTIONS–Three different workloads of steady state cycling ergometry: control state without cycling, cycling at a target heart rate of 100 beats/min, and cycling at a target heart rate of 150 beats/min. Intravenous infusion of atropine (target heart rate 100 beats/min) followed by the additional infusion of adrenaline and noradrenaline. MAIN OUTCOME MEASURES–Fast Fourier analysis of heart rate variability; blood pressure; and venous plasma concentrations of lactate, adrenaline, and noradrenaline. RESULTS–During the control exercise period there were no changes in the assessed variables compared with the preceding resting period. During exercise at a heart rate of 100 beats/min systolic blood pressure increased and heart rate variability decreased. During exercise at a heart rate of 150 beats/min systolic blood pressure and lactate, adrenaline, and noradrenaline concentrations increased. In addition, low frequency (LF) was lower than during exercise at 100 beats/min, high frequency (HF 0.15-0.80 Hz) resembled that during exercise at 100 beats/min, and diastolic blood pressure was reduced. Infusion of atropine caused no changes in blood pressure or plasma concentrations of lactate, adrenaline, and noradrenaline and decreased heart rate variability. The additional infusion of adrenaline and noradrenaline completely suppressed heart rate variability and increased blood pressure. CONCLUSIONS–The reduction in LF and HF during exercise at a heart rate of 100 beats/min, which is not characterised by increased plasma catecholamine concentrations, and during atropine infusion suggests that heart rate variability in the supine state is largely influenced by vagal activity. The additional reduction in LF during exercise at 150 beats/min and during catecholamine infusion may reflect a negative feedback of circulating catecholamines on the sympathetic control of heart rate.